187k views
2 votes
6(2m-3)-3m=2m-18+m what is m?

2 Answers

2 votes

6(2m−3)−3m=2m−18+m

Step 1: Simplify both sides of the equation.

6(2m−3)−3m=2m−18+m

(6)(2m)+(6)(−3)+−3m=2m+−18+m(Distribute)

12m+−18+−3m=2m+−18+m

(12m+−3m)+(−18)=(2m+m)+(−18)(Combine Like Terms)

9m+−18=3m+−18

9m−18=3m−18

Step 2: Subtract 3m from both sides.

9m−18−3m=3m−18−3m

6m−18=−18

Step 3: Add 18 to both sides.

6m−18+18=−18+18

6m=0

Step 4: Divide both sides by 6.

6m

6

=

0

6

m=0

User Emine
by
7.0k points
5 votes

6(2m-3)-3m=2m-18+m

distribute

12m-18 -3m = 2m-18 +m

combine like terms

9m-18 =3m-18

subtract 3m from each side

6m -18 = -18

add 18 to each side

6m =0

divide by 6

m=0

User Afruzan
by
6.6k points